2018
DOI: 10.1063/1.5020694
|View full text |Cite
|
Sign up to set email alerts
|

Polarization imprint effects on the photovoltaic effect in Pb(Zr,Ti)O3 thin films

Abstract: The polarization imprint along with the photovoltaic (PV) effect has been studied in Pt/ Pb(Zr 0.3 Ti 0.7)O 3 /SrRuO 3 ferroelectric capacitors. It is shown that the positive DC poling induces the imprint with a downward direction whereas the negative DC poling suppresses the imprint (i.e., rejuvenation). In the polarization up state, the imprinted capacitor exhibits degraded PV properties compared with the rejuvenated one. This may be because the imprint reduces the number of upward domains, thus lowering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…26,27 Comparing the XRD results of CSed and SPSed samples, it can be found that the sample prepared by SPS contains higher content of T phase, due to the value of I(002)/I(200) of the T phase between 44 and 46 is 1 : 2, and the peak of the SPSed samples is closer to 1 : 2 here. [28][29][30] In addition, as shown in Fig. 1(g) and (h), the R-phase characteristic peak of CSed ceramic more higher than that of SPSed ceramic, indicating the more R phase shows in CSed ceramic.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…26,27 Comparing the XRD results of CSed and SPSed samples, it can be found that the sample prepared by SPS contains higher content of T phase, due to the value of I(002)/I(200) of the T phase between 44 and 46 is 1 : 2, and the peak of the SPSed samples is closer to 1 : 2 here. [28][29][30] In addition, as shown in Fig. 1(g) and (h), the R-phase characteristic peak of CSed ceramic more higher than that of SPSed ceramic, indicating the more R phase shows in CSed ceramic.…”
Section: Methodsmentioning
confidence: 81%
“…It is generally believed that the coercive eld is related to the exibility of domain and domain walls, and the coercive eld of T-phase is generally larger than that of R-phase. 29 SPS ceramic shows higher E C (1.49 kV mm À1 ) than CS ceramic (0.92 kV mm À1 ). This phenomenon is consistent with their XRD conclusions, and the XRD of SPS shows more obvious T-phase.…”
Section: Measurement Of Electrical Propertiesmentioning
confidence: 88%
“…In recent years, the photovoltaic effect of ferroelectric materials, such as Pb(Zr,Ti)O 3 [6], BaTiO 3 [7,8] and BiFeO 3 [9,10,11], have attracted a lot of research for photovoltaic application. Among many ferroelectric materials, BiFeO 3 (BFO) is the most representative [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Another key feature of the saturated loops is the negligible voltage offset, namely, the positive and negative coercive voltages are almost symmetric, suggesting that there is only small or even no imprint field. Because the imprint field typically originates from the defects 38,39 , its absence in turn verifies the high quality of our epitaxial PZT film. Besides, the absence of imprint field contributes to the symmetry of switchable photovoltaic responses 38,40 (to be shown later).…”
Section: Resultsmentioning
confidence: 69%